MATURATION OF INTRA-OVARIAN EGGS AND SPAWNING PERIODICITIES IN SOME FISHES - Prabhu, M S (Indian Journal of Fisheries, 2015)
A series of changes are undergone by the intra-ovarian eggs before they become mature and attention has already been paid to their development and accounts have been given by various earlier authors. As early as in 1899, Fulton observed that the occurrence, in large numbers, of ova of intermediate size, between the small immature ova and the bigger yolky ones, in mature fishes, is closely associated with a prolonged spawning period. An attempt to study the maturity by the measurements of the ova was first made by Clark (1934) on the California sardine (Sardina carulea). Later, Hickling and Rutenberg (1936) determined the spawning periods in hake, haddock, pilchard, herring and lepidogaster by the same method. Recently De Jong (1939) has investigated, on the same lines the spawning habits of 13 species of teleostean fishes from the Java sea.